AKUN SOSIAL MEDIA SEBAGAI OBJEK ASURANSI - Muhammad Lukman Nurhakim (UNES Law Review, 2023)
The development of the digital era has made various aspects of sosial media expand in terms of function and technology. Sosial media is no longer just a tool for sosializing but has also developed as a driving force for the economic sector. The ease of interacting with various groups is used by various parties to gain benefits, one of the parties who experience these benefits is sosial media influencers. Those who have influence in cyberspace with the number of followers, make sosial media a tool to earn income. This phenomenon makes the ownership of a sosial media account have economic value, this paradigm makes the ownership of a sosial media account cannot escape the threat of crime. This study examines the risks associated with owning a sosial media account and whether ownership of a sosial media account can be used as an object in an insurance agreement. This research is a normative legal research using statutory and conceptual approaches. Based on the research conducted, it can be concluded that ownership of sosial media accounts can be insured based on the Commercial Code, Law Number 40 of 2014 concerning Insurance, as well as the theory of applicable insurance law.